Characterization of lithium-based solid polymer electrolytes - Barbosa, P. C. (2009)
Sol-gel derived poly(oxyethylene)/siloxane hybrids doped with lithium hexafluoroantimonate, LiSbF6, have been prepared. Compositions of these novel xerogel electrolytes were identified using the conventional d-U(2000)nLiSbF6 notation, (where n is the molar ratio of oxyethylene moieties per Li+ ion) and samples with n between ∞ and 2.5 were characterized by conductivity measurements, cyclic voltammetry at a gold microelectrode and thermal analysis. The electrolyte films produced were obtained as transparent and amorphous monoliths with encouraging electrochemical and thermal properties.